Effect of cyclic martensitic γ-ε transformations on diffusion characteristics of cobalt in an iron–manganese alloy - Danilchenko, V.Yu.; Mazanko, V.F.; Filatov, O.V.; Iakovlev, V.E. (Успехи физики металлов, 2019)
This review article analyses the results of experimental investigations of the influence of the cyclic direct γ−ε (f.c.c.–h.c.p.) and reverse ε−γ (h.c.p.–f.c.c.) martensitic transformations (MT) on the diffusion characteristics of Co atoms in Г18С2 (Fe–18.3 wt.% Mn–2.1 wt.% Si) alloy with low stacking-fault energy.